2020
DOI: 10.1371/journal.pone.0238631
|View full text |Cite
|
Sign up to set email alerts
|

The EDN2 rs110287192 gene polymorphism is associated with paratuberculosis susceptibility in multibreed cattle population

Abstract: Paratuberculosis (pTB), also known as Johne's disease (JD), is a contagious, chronic, and granulomatous inflammatory disease of the intestines of ruminants which is caused by Mycobacterium avium subsp. paratuberculosis (MAP) infection, resulting in billions of dollars in economic losses worldwide. Since, currently, no effective cure is available for MAP infection, it is important to explore the genetic variants that affect the host MAP susceptibility. The aim of this study was to analyze a potential associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…EDN2 is a transcriptionally regulated 177 amino acid peptide implicated in vascular homeostasis, but also in female reproduction (Ko et al, 2012), gastrointestinal function (Chang et al, 2013; Takizawa et al, 2005), immune cell function (Grimshaw et al, 2002), heart failure (Brown et al, 2000) and various cancers (Ling et al, 2013). In bovines, EDN2 expression has been found to be affected in lung epithelial cells during respiratory diseases, specifically in paratuberculosis infection (Çınar et al, 2020; Kiser et al, 2021), and in bronchial epithelial cells after exposure to viral (Herpes virus) and bacterial ( Mannheimia haemolytica ) pathogens (N'jai et al, 2013). Thus, the lesions compatible with a respiratory viral process found in the five necropsied calves could have been facilitated by the alteration of the expression of EDN2 triggering bovine GRL.…”
Section: Discussionmentioning
confidence: 99%
“…EDN2 is a transcriptionally regulated 177 amino acid peptide implicated in vascular homeostasis, but also in female reproduction (Ko et al, 2012), gastrointestinal function (Chang et al, 2013; Takizawa et al, 2005), immune cell function (Grimshaw et al, 2002), heart failure (Brown et al, 2000) and various cancers (Ling et al, 2013). In bovines, EDN2 expression has been found to be affected in lung epithelial cells during respiratory diseases, specifically in paratuberculosis infection (Çınar et al, 2020; Kiser et al, 2021), and in bronchial epithelial cells after exposure to viral (Herpes virus) and bacterial ( Mannheimia haemolytica ) pathogens (N'jai et al, 2013). Thus, the lesions compatible with a respiratory viral process found in the five necropsied calves could have been facilitated by the alteration of the expression of EDN2 triggering bovine GRL.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of SNP208 to be associated with MAP infection across breeds in different parts of the world provides further evidence that this region surrounding EDN2 is associated with the disease. Çinar et al ( 48 ) also investigated SNP272, SNP208, and SNP105 for their roles in MAP infection and identified SNP208 to be associated with MAP infection in East Anatolian Red crossbred cattle, Anatolian Black crossbred cattle, and Holstein cattle. Çinar et al ( 48 ) found that MAP infection differed between animals with different genotypes at SNP208 ( P < 0.05) where cattle with the TG or GG genotypes were more often controls and cattle with TT genotypes were cases, suggesting that animals with the G may be less susceptible to MAP infection.…”
Section: Discussionmentioning
confidence: 99%
“…Çinar et al ( 48 ) also investigated SNP272, SNP208, and SNP105 for their roles in MAP infection and identified SNP208 to be associated with MAP infection in East Anatolian Red crossbred cattle, Anatolian Black crossbred cattle, and Holstein cattle. Çinar et al ( 48 ) found that MAP infection differed between animals with different genotypes at SNP208 ( P < 0.05) where cattle with the TG or GG genotypes were more often controls and cattle with TT genotypes were cases, suggesting that animals with the G may be less susceptible to MAP infection. Çinar et al ( 48 ) did not identify any differences in MAP infection for SNP105 or SNP272.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published data argue the link between MAP susceptibility, disease severity, and genetic predisposing factors (Begg et al, 2017, Reddacliff et al, 2005, Koets et al, 2000. Differences in disease susceptibility and immune response could be recognized even among individual animals within the same breed in beef cattle (Çınar et al, 2020, Juste et al, 2018, Begg et al, 2017), dairy cows (Berry et al 2010,small ruminants (Mortensen et al, 2004, Sorge et al, 2011, and deer (Vázquez et al, 2014).Genome analysis revealed a link between MAP susceptibility and the presence of heterozygous alleles in cis-eQTL-rs43744169 (T/C), cis-eQTL-rs110345285 (C/C), and cis-eQTL rs109859270 (C/T), which influence the expression level of eukaryotic elongation factor 1-α2 (eEF1A2), MDS1 and EVI1 of (MECOM) complex (Canive et al, 2021). Animals harboring these genetic markers should be excluded from the herds, and only resistant animals are reared as a part of running JD control programs (Ruiz-Larrañaga et al, 2010a, Ruiz-Larrañaga et al, 2010b.…”
Section: Exclusion Of Genetically Susceptible Breeds From the Herdsmentioning
confidence: 99%